U-PB GEOCHRONOLOGY OF SPELEOTHEMS BY MC-ICPMS - Woodhead J.; Hellstrom J.; Maas R.; Drysdale R.; Zanchetta G.; Devine P.; Taylor E. (My University, 2006)
Building upon the work of Richards et al. [1998. U-Pb dating of a speleothem of Quaternary age. Geochimica et Cosmochimica Acta 62, 3683-3688], we have developed a method for precise dating of speleothems beyond the range of the U-Th technique using the U-Pb decay scheme. By coupling low-blank sample preparation procedures and multi-collector inductively coupled plasma mass spectrometry (MC-ICPMS) analytical methodologies developed for low-level Pb-isotope analysis, we find that, under ideal circumstances (radiogenic speleothems with very low common Pb), U-Pb dating of speleothems is not only possible, but also produces excellent age resolution-often comparable to or better than U-Th studies. Corrections for initial isotopic disequilibrium are necessary and exert a strong control on the achievable age uncertainty. The technique will be of immediate benefit in extending speleothem-based climate proxy records beyond ∼500 ka and will also find other uses, such as the dating of associated sub-fossil remains, and providing constraints on rates of landscape evolution and neo-tectonic processes. Here we present initial results for speleothems from the Nullarbor Plain, Western Australia, and the Alpi Apuane, Italy. The Nullarbor samples provide important new constraints on the development of aridity in Australia during the late Tertiary/early Quaternary, while the Apuane samples offer insights into the landscape history and uplift of that region.
Keywords: Cenozoic::Quaternary; Кайнозой::Четвертичная